Integrating Hifz Al-Bi'ah from Abdul Majid An-Najjar into Fatwas and Plastic Waste Management Policies in Indonesia - Hisan, Khairatun; Budiwati, Anisah; Haqqiya, Hannafa (Program Studi Hukum Keluarga Islam, 2026)
This study examines the philosophical coherence and practical effectiveness of Indonesia’s plastic waste management policies through Abdul Majid An-Najjar’s concept of hifz al-bi'ah within the contemporary Maqasid al-Shariah framework. Despite the enactment of government regulations and religious edicts to address the growing plastic waste crisis, few studies have evaluated these policies using hifz al-bi'ah as an analytical framework. This study aims to assess the relevance and implementation of Indonesia’s plastic waste policies based on An-Najjar’s theory. Employing a normative-juridical and philosophical approach, this qualitative library research analyzes Law No. 18 of 2008, Minister of Environment and Forestry Regulation No. P.75/2019, and MUI Fatwa No. 41 of 2014 through qualitative content analysis. The findings indicate that these legal instruments reflect four principles of hifz al-bi'ah: protection from environmental damage, pollution, excessive consumption, and environmental revitalization. However, policy implementation remains ineffective due to the dominance of end-of-pipe waste management, weak enforcement of Extended Producer Responsibility obligations, and the non-binding legal status of religious fatwas. The study concludes that stronger regulatory enforcement and integrated environmental governance are necessary to realize the objectives of hifz al-bi'ah in Indonesia.